2002
DOI: 10.1103/physreve.66.031201
|View full text |Cite
|
Sign up to set email alerts
|

Soret coefficient for liquid argon-krypton mixtures via equilibrium and nonequilibrium molecular dynamics: A comparison with experiments

Abstract: The Soret and the other transport coefficients, characterizing the heat and mass transport in binary mixtures, have been obtained by equilibrium and nonequilibrium molecular dynamics (EMD and NEMD, respectively). Two state points of the argon-krypton mixture are considered, for which experimental values of the Soret coefficient are available. To attempt a comparison between simulations and experiments the common enthalpy-diffusion-free expression for the heat flux has been chosen. The comparison of the simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 21 publications
2
56
0
Order By: Relevance
“…However, our goal here is to probe the methodology, thus, we decided to avoid long-range corrections to pressure by using a modified Lennard-Jones potential such that forces vanish at the cut-off. Thus, we used splined forces [12,32] such that the force acting between atoms is a Lennard-Jones force if the distance between the atoms is lower than the spline radius and has a cubic polynomial form in between the spline and the cut-off radii. We used a cut-off radius of 3.5 and a spline radius of 2.5.…”
Section: Simulationsmentioning
confidence: 99%
“…However, our goal here is to probe the methodology, thus, we decided to avoid long-range corrections to pressure by using a modified Lennard-Jones potential such that forces vanish at the cut-off. Thus, we used splined forces [12,32] such that the force acting between atoms is a Lennard-Jones force if the distance between the atoms is lower than the spline radius and has a cubic polynomial form in between the spline and the cut-off radii. We used a cut-off radius of 3.5 and a spline radius of 2.5.…”
Section: Simulationsmentioning
confidence: 99%
“…Another route is based on equilibrium MD simulations [15][16][17]21,25,26]. Statistical mechanics is able to provide a general expression for the heat of transport in terms of an integral of the time correlation function between heat flux and matter flux evaluated for the system in thermodynamic equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, theoretical modelling of thermotransport still lacks a clear and convincing fundamental understanding of the process at the atomistic level. Accordingly, computer simulation techniques such as molecular dynamics (MD) which operate at the atomistic level are useful for obtaining valuable insight into the thermotransport phenomenon [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…6,9,15,16 Molecular dynamics (MD) simulations have become an important tool in the investigation of thermal diffusion behavior of Lennard-Jones model fluids and small-molecule liquids. [17][18][19][20][21] Lately, the simulation techniques for non-equilibrium properties have been improved, which have led to a reasonable agreement between simulations and experiments for associating and non-associating liquid mixtures. [21][22][23] Simulations and also a two-chamber lattice model calculation have shown that the relation between the cross interactions and the pure interactions determine whether the sign of the Soret coefficient changes with concentration.…”
Section: Introductionmentioning
confidence: 99%